2002
DOI: 10.2307/1468410
|View full text |Cite
|
Sign up to set email alerts
|

N uptake as a function of concentration in streams

Abstract: Detailed studies of stream N uptake were conducted in a prairie reach and gallery forest reach of Kings Creek on the Konza Prairie Biological Station. Nutrient uptake rates were measured with multiple short-term enrichments of NO 3 Ϫ and NH 4 ϩ at constant addition rates in the spring and summer of 1998. NH 4 ϩ uptake was also measured with 15 N-NH 4 ϩ tracer additions and short-term unlabeled NH 4 ϩ additions at 12 stream sites across North America. Concurrent addition of a conservative tracer was used to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
209
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 232 publications
(225 citation statements)
references
References 29 publications
11
209
2
3
Order By: Relevance
“…This response may differ from responses to acute pulses of NO 3 -concentration, which may not follow the same pattern observed here. Dodds et al (2002) reported a 1st order response to short NO 3 -additions on Kings Creek, while O'Brien (2006) observed saturation of NO 3 -uptake in response to short-term addition experiments in three prairie streams. Thus the response of an individual stream to temporal increases in NO 3 -may follow the Michaelis-Menten or 1st order models, but the response across streams with chronic NO 3 -inputs is best described with the Efficiency Loss model.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This response may differ from responses to acute pulses of NO 3 -concentration, which may not follow the same pattern observed here. Dodds et al (2002) reported a 1st order response to short NO 3 -additions on Kings Creek, while O'Brien (2006) observed saturation of NO 3 -uptake in response to short-term addition experiments in three prairie streams. Thus the response of an individual stream to temporal increases in NO 3 -may follow the Michaelis-Menten or 1st order models, but the response across streams with chronic NO 3 -inputs is best described with the Efficiency Loss model.…”
Section: Modelmentioning
confidence: 99%
“…But phosphorus uptake or growth experiments in streams (Bothwell 1989;Mulholland et al 1990) and lakes (Dodds 1995) reveal half-saturation constants for uptake or growth for assemblages that are far greater than those exhibited by individual organisms in laboratory culture. The rates of ammonium (NH 4 + ) uptake, NO 3 -uptake, nitrification, and denitrification do not always saturate in prairie streams (Dodds et al 2002;Kemp and Dodds 2002b). Furthermore, even if short-term increases in N cause saturation, the influence of chronic N increases is not well characterized across systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to empirical methods (e.g., Webster and Ehrman 1996), we determined S w by regressing plateau concentrations against distance, after correcting for background and dilution. A total of 6 simulations were performed with increasing levels of solute addition, from which we estimated S w at background concentration through extrapolation (similar to the approach suggested by Dodds et al 2002). Uptake rate constant (K c ), uptake rate (U) and uptake velocity (V f ) were calculated subsequently using Eq.…”
Section: Ammonium Uptake Metricsmentioning
confidence: 99%
“…However, the observed K s values for NH 4 + and NO 3 2 uptake in our study fall within the range of values that have been reported in the literature. Dodds et al (2002) reported a K s of 64 mg NH 4 + -N/L for a prairie reach of Kings Creek, whereas Kemp and Dodds (2002b) projected whole-stream K s of 12.3 mg/L for NO 3 2 and 6.7 mg/L and NH 4 + based on uptake kinetics of different substratum types within the stream. Payn et al (2005) reported K s in forested streams of 6 mg NH 4 + -N/L for Ball Creek, North Carolina (USA), and 14 mg NH 4 + -N/L for Walker Branch, Tennessee (USA).…”
mentioning
confidence: 99%